(untitled) (Revista Innova Educación, 2025)
Currently, with the advancement of technology and the accelerated dissemination of information, it is essential to have the ability to discern verifiable content from speculative information; therefore, developing critical thinking is necessary, as it allows for the thorough analysis and evaluation of such information. In this study, the objective was to identify the relationship between learning styles and critical thinking among secondary-level students from a private educational institution in Ate, Lima. Methodologically, the research followed a quantitative approach, was basic in nature, and employed a descriptive-correlational design. The population consisted of 123 secondary-level students, and the sample was census-based. The survey technique was used, and the questionnaire served as the instrument. Among the results, it was found that correlations between critical thinking and the theoretical, pragmatic, and active styles were high, while with the reflective style they were moderate. It is concluded that learning styles are positively related to critical thinking. These findings invite reconsideration of learning styles, as they are not profiles that confine students but starting points for designing demanding experiences that integrate evidence, criteria, and self-regulation. This, in turn, implies a school that makes intellectual decisions visible, promotes virtues, and expands students’ capacity for agency to transfer such judgment into academic, professional, and civic life.